Pendidikan Berkelanjutan Berbasis Konservasi dan Teknologi Sebagai Aksi Nyata Dalam Mewujudkan SDGs - Faizah, Auliya Nurul; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This article aims to examine the role of conservation and technology-based sustainable education in realizing the Sustainable Development Goals (SDGs). Using qualitative methods and a descriptive approach, this research explores various related literature to gain an in-depth understanding of the concepts, challenges and potential for implementing sustainable education in the context of the SDGs. Through analysis of literature studies, this article highlights the importance of integrating sustainable education that focuses on environmental conservation and the application of technology as a concrete effort in achieving the SDGs. Sustainable education builds the capacities and skills needed to achieve holistic sustainable development. The challenges and obstacles faced in implementing sustainable education are accessibility, lack of awareness, lack of resources, curriculum changes, and technological challenges. However, with cross-sector collaboration, political commitment, and innovation in the use of technology and learning approaches, efforts to realize sustainable education based on conservation and technology as real action in achieving the SDGs are possible.